AUDIT KURIKULUM TERHADAP KESESUAIAN ANTARA PERENCANAAN DAN PELAKSANAAN PEMBELAJARAN DI MA YPMI WANAYASA: - Isnawati; Fauziah, Yunisa; Mutaqin, Muhamad Zaenal (Expectation: Journal of Islamic Education Management, 2025)
This study aims to analyze the alignment between lesson planning and learning implementation through curriculum audit at MA YPMI Wanayasa. This research employed a qualitative approach with data collection techniques including interviews, observations, and document analysis. The data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that there are discrepancies between planning and implementation of learning, which are caused by the dense curriculum content, the limited number of teachers, excessive teaching workload, and the mismatch between teachers’ qualifications and the subjects taught. The curriculum audit also shows that several indicators have not been optimally fulfilled. Improvement efforts that can be implemented include reorganizing teachers’ workload, mapping teacher needs, enhancing teacher competencies, and developing more realistic and flexible lesson plans to improve the alignment between planning and learning implementation.